2003
DOI: 10.1046/j.1365-8711.2003.06135.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth and structure of dark matter haloes

Abstract: In this paper, we analyse in detail the mass-accretion histories and structural properties of dark haloes in high-resolution N-body simulations. We model the density distribution in individual haloes using the Navarro-Frenk-White (NFW) profile. For a given halo, there is a tight correlation between its inner-scale radius r s and the mass within it, M s , for all its main progenitors. Using this correlation, one can predict quite well the structural properties of a dark halo at any time in its history from its … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
286
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(328 citation statements)
references
References 28 publications
39
286
3
Order By: Relevance
“…This characteristic scale factor a = ac is the point when the logarithmic mass accretion rate, d log M/d log a, falls below a critical value S = 2 (Wechsler et al 2002). Similar results were found by Zhao et al (2003a; using high-resolution simulations and by van den Bosch (2002) using extended Press-Schechter theory. In a cosmological spherical collapse model, the shell collapse time is determined by the mean initial over-density within the mass shell; the mass within a mass shell collapses when the average linear over-density (calculated using linear perturbation theory) reaches δc ≈ 1.686.…”
Section: Initial Conditions and Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…This characteristic scale factor a = ac is the point when the logarithmic mass accretion rate, d log M/d log a, falls below a critical value S = 2 (Wechsler et al 2002). Similar results were found by Zhao et al (2003a; using high-resolution simulations and by van den Bosch (2002) using extended Press-Schechter theory. In a cosmological spherical collapse model, the shell collapse time is determined by the mean initial over-density within the mass shell; the mass within a mass shell collapses when the average linear over-density (calculated using linear perturbation theory) reaches δc ≈ 1.686.…”
Section: Initial Conditions and Methodssupporting
confidence: 80%
“…NFW conjectured that the dependence of halo concentration parameter on halo mass could be explained by the assembly of more massive halos at later times than lower-mass halos. Later, Wechsler et al (2002) and Zhao et al (2003a; found that the concentration of a halo depends on the assembly history. Together, these results suggest that CDM initial conditions play an important role in determining halo density profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmological simulations show that the halo concentration depends on both halo mass and redshift at which the halo is identified (e.g. Bullock et al 2001;Eke, Navarro & Steinmetz 2001;Zhao et al 2003Zhao et al , 2009Macciò et al 2007). Here we adopt the recent simulation result of Prada et al (2012) to compute c for a halo with a given mass at a given redshift.…”
Section: Formation History and Structure Of Dark Matter Halosmentioning
confidence: 99%
“…First, the halo growth has been recognized (see Zhao et al 2003;Wechsler et al 2006;Hoffman et al 2007;Diemand et al 2007) to comprise two stages: an early fast collapse including a few violent major mergers, that builds up the halo main "body" with the structure set by dynamical relaxation; and a later, quasi-equilibrium stage when the body is nearly unaffected, while the outskirts develop from the inside-out by minor mergers and smooth accretion (see Salvador-Solé et al 2007). The transition is provided by the time when a DM gravitational potential attains its maximal depth; i.e., the radial peak of the circular velocity v 2 c ≡ GM/R attains its maximal height, along a given growth history (see Li et al 2007).…”
Section: Two-stage Evolutionmentioning
confidence: 99%